Application of PS-InSAR Method for the Land Subsidence Analysis Using StaMPS (Case Study : Gresik Regency) - Rizki Fahrudin Ulin; Muhammad Taufik; Ira Mutiara Anjasmara (IPTEK Journal of Proceedings Series, 2019)
Land Subsudence often occurs in various regions around the world, especially big cities and coastal areas. The poor impact of land subsidence may the destruction of a region's infrastructure which caused by excessive water taking for industrial use and existing soil forming structures in the area. Therefore, it is necessary to find various inventions with the aim to mitigate natural disasters accurately. Along with the development of technology, then used adequate technology that has wide area capability. The selection of PS-InSAR method based on Radar becomes the best solution because it has good accuracy and decrease the decorrelation effect. The method used by PS-InSAR in the process of land subsidence in Gresik Regency using StaMPS at the same time with the decrease of ground level between -49.35 mm / year to 54,95 mm / year. Bungah Sub-district has the maximum value from the period before May 2015 to January 2016.